Sociedad racional y educación: la génesis de la racionalidad educativa modernista - Guillermo Miranda-Camacho (Revista Electrónica Educare)
The objective of this article is to explore some aspects related to the origin of modern education rationality. The study is based on the analysis of different dimensions of the dialectical interaction historically established between the rational logic behind the structural changes of the capitalist society and the construction of the modern liberal education perspective. With the purpose of defining the keys to the process, the first section provides a brief reference to the foundations of the origin of rational thinking and those of modernity, which was caused by the secularization process suffered by the universe of the renaissance culture. In the second part we discuss some dimensions of illustrations and the encyclopedia as basic cultural and education projects in the rational organization of society in the XVIII century. The third section explores some dimensions of the connection between capitalist modernization and educational rationality through some of the main historical factors: the creation of State-nations, nationality and citizenship, the rationality of liberal capitalism, the universality and ethnocentrism of the elite culture, the instrumental reason and the view of progress as technical evolution. In addition, we highlight the State’s adoption of education as part of the construction of the public sphere by emphasizing the rational and legitimating role that lies at the basis of these historical processes. Finally, the fourth section analyzes how the creation of modern rationality takes on a historical view of social progress neglecting humanistic ethics. This process influences the emergence of an educational rationality based on the ideological justification of inequality and on a meritocratic view of the rational society, as Tourine has defined it (1993).